Comparison of three scales (BIS, SUMD and BCIS) for measuring insight dimensions and their evolution after one-year of follow-up: Findings from the FACE-SZ Cohort. (September 2021) - Capdevielle, Delphine; Norton, Joanna; Aouizerate, Bruno; Berna, Fabrice; Chereau, Isabelle; D'Amato, Thierry; Dubertret, Caroline; Dubreucq, Julien; Fond, Guillaume; C, Lançon; Mallet, Jasmina; Misdrahi, David; et al.
Highlights: Few studies have compared self-report measures and clinician-rated instruments for clinical insight and cognitive insight. The natural course of insight and its different measures are poorly understood. Good overall agreement between the two clinical insight instruments was found. Agreement between cognitive and clinical insight was moderate. The evolution of cognitive insight was not congruent with clinical insight evolution. Abstract: The aim of our study was to compare the performance of three different instruments measuring clinical and cognitive dimensions of insight. Data on 182 outpatients with schizophrenia and one-year follow-up assessments was drawn from the FACE-SZ cohort. Awareness of clinical state (« clinical insight ») was measured using both a clinician-rated measure (the Scale to assess Unawareness of Mental Disorder (SUMD)), and a self-report measure (the Birchwood Insight Scale (BIS). Cognitive insight was measured using a self-report measure (the Beck Cognitive Insight Scale (BCIS)). For each scale, change in insight was examined at the follow-up. Correlations between SUMD and BIS subscales measuring same dimensions were significant. BIS-BCIS correlations were weak for all combinations except between BIS illness dimension and BCIS composite score. At the follow-up, BIS and SUMD awareness of treatment need improved whereas illness and symptom awareness increased only on the SUMD. Conversely, cognitive insight composite scores decreased. Despite relatively good overall agreement between the two clinical insight instruments, considerable variability for similar insight dimensions measured by different instruments was found. Agreement between cognitive and clinical insight is moderate. Our study strengthens the argument that insight is harder to operationalize than other symptoms and may explain why it is so seldom explicitly targeted in schizophrenia treatment.